Sidarling: Pengolahan Sampah Organik menjadi Ecoenzyme - Handayani, Rika; Syarifah, Laylatus; Inggil, Nafis Sulthan; Prasasti, Agustin Oldri; Anjelita, Rina Okselya; Damayanti, Tariska Eka; Layla, Alia Nur; Rahman, Askur (Jurnal Pemberdayaan Umat, 2024)
Purpose: This training aims to provide education to the people of Banyuajuh Village, especially to KDP housewives in order to reduce waste, especially organic waste in Banyuajuh village. Methodology/approach: The learning method carried out in this SIDARLING activity is by lecture method as well as independent practice and practice. This training was conducted by housewives, before and after conducting the training and also postest and pretest were held to measure the knowledge and understanding of housewives in Banyuajuh Village, Kamal sub-district, Bangkalan regency. Results/findings: This training was welcomed by Banyuajuh village housewives enthusiastically, this is evidenced by housewives who practice independently in every RW in Banyuajuh village. This SIDARLING activity is very helpful for housewives in reducing and processing waste, especially organic waste. Housewives can make ecoenzyme independently and the results of ecoenzyme housewives during overall mentoring have good results and the results of the postest and pretest can be said that mothers can respond to the material quickly, and are very active in conveying ideas. Limitations: This SIDARLING activity is very far-reaching so that there needs to be a limit to the problem, making this ecoenzyme can be done for environmental awareness for housewives so that the waste contained in the homes of housewives can be processed by themselves. Processing organic waste into ecoenzyme and can be processed again into derivative products. Contribution: This activity was carried out by providing training to PKK housewives in Banyuajuh Village, by produced ecoenzyme from organic waste. Organic waste is one type of waste that is often disposed of and not used properly, so SIDARLING can make housewives aware to process organic waste into ecoenzymes.